2021
DOI: 10.1108/ejm-02-2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

Netnography and design thinking: development and illustration in the vegan food industry

Abstract: Purpose This paper aims to strengthen the process of design thinking by aligning it with netnography, specifically auto-netnography, which this paper asserts is particularly suited to the task of studying and enriching the actions of “designerly types” who seek to fashion monetisable businesses. Design/methodology/approach This paper conducts an auto-netnography with a structure divined from established design thinking theory – that of empathising, defining, ideating, prototyping and testing – to afford an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Also, these findings can lead consumers on the path to food well-being that is a collaborative venture between consumers and food providers (Bogomolova et al , 2021). In this vein, marketers and regulators can also interact with customers to co-create products that meet their needs (Ashman et al , 2021), or stimulating insights on consumers’ interpretation of the food label (Machin et al , 2021). In a context where health “is used by marketers to idealize, embellish, and highlight the positive aspects of the food industry over the more controversial ones” and to connect with other concerns such as sustainability and nutrition (Silchenko and Askegaard, 2021), FOPL could support proper informed choice about the real composition of the product and move consumers towards healthier food choices.…”
Section: Discussionmentioning
confidence: 99%
“…Also, these findings can lead consumers on the path to food well-being that is a collaborative venture between consumers and food providers (Bogomolova et al , 2021). In this vein, marketers and regulators can also interact with customers to co-create products that meet their needs (Ashman et al , 2021), or stimulating insights on consumers’ interpretation of the food label (Machin et al , 2021). In a context where health “is used by marketers to idealize, embellish, and highlight the positive aspects of the food industry over the more controversial ones” and to connect with other concerns such as sustainability and nutrition (Silchenko and Askegaard, 2021), FOPL could support proper informed choice about the real composition of the product and move consumers towards healthier food choices.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research could be conducted to answer which tools are most effective in specific situations or industries. Early studies on emerging tools should proceed, including using new technologies, such as augmented and virtual reality (Earle and Leyva-de la Hiz, 2020) or netnography, a digital derivative of ethnography for application in social media (Ashman et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been defined as ethnographic research conducted in a virtual environment via and for the Internet or using different data collection tools in a virtual environment on the Internet. It is believed that such long-term, immersive online participatory observation allows the researcher access to the inner vision of the culture holders (Ashman et al, 2021). Netnographic studies in China began in the last 20 years and have shown a rapid rise with the prevalence of mobile social media platforms.…”
Section: Netnography Research Of Online Subculturesmentioning
confidence: 99%